Development of Human Cell-Based In Vitro Infection Models to Determine the Intracellular Survival of Mycobacterium avium - Kilinç, Gül; Walburg, Kimberley V.; Franken, Kees L. M. C.; Valkenburg, Merel L.; Aubry, Alexandra; Haks, Mariëlle C.; Saris, Anno; Ottenhoff, Tom H. M. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium avium (Mav) complex accounts for more than 80% of all pulmonary diseases caused by non-tuberculous mycobacteria (NTM) infections, which have an alarming increase in prevalence and varies in different regions, currently reaching 0.3-9.8 per 100.000 individuals. Poor clinical outcomes, by cause of increasing microbial drug-resistance and low treatment adherence due to drug-toxicities, emphasize the need for more effective treatments. Identification of more effective treatments, however, appears to be difficult, which may be due to the intracellular life of NTM and concomitant altered drug-sensitivity that is not taken into account using traditional drug susceptibility testing screenings. We therefore developed human cell-based in vitro Mav infection models using the human MelJuSo cell line as well as primary human macrophages and a fluorescently-labelled Mav strain. By testing a range of multiplicity of infection (MOI) and using flow cytometry and colony-forming unit (CFU) analysis, we found that a MOI of 10 was the most suitable for Mav infection in primary human macrophages, whereas a MOI of 50 was required to achieve similar results in MelJuSo cells. Moreover, by monitoring intracellular bacterial loads over time, the macrophages were shown to be capable of controlling the infection, while MelJuSo cells failed to do so. When comparing the MGIT system with the classical CFU counting assay to determine intracellular bacterial loads, MGIT appeared as a less labor-intensive, more precise and more objective alternative. Next, using our macrophage-Mav infection models, drug efficacy of first-line drug rifampicin and more recently discovered bedaquiline on intracellular bacteria was compared to activity on extracellular bacteria. The efficacy of the antibiotics inhibiting bacterial growth was significantly lower against intracellular bacteria compared to extracellular bacteria. This finding emphasizes the crucial role of the host cell during infection and drug-susceptibility and highlights the usefulness of the models. Taken together, the human cell-based Mav infection models are reliable tools to determine intracellular loads of Mav, and which will enable to investigate host-pathogen interactions and to evaluate the efficacy of (host-directed) therapeutic strategies against Mav.